POTENTIAL GENDER DIFFERENCES IN PATHOPHYSIOLOGY OF MIGRAINE AND TENSION TYPE HEADACHE - Restu Susanti (Universitas Fort De Kock, 2020)
Headache is one of the most common symtomps which cause patients consult a neurologist. Primary headache is headache without other underlying diseases. Primary headaches can be divided into migraine headaches, tension types-headache, trigeminal autonomic cephalalgias, and other types of headaches. Sex differences play a role in the perception of headache. Theories regarding hormonal, the number of pain-sensitive points, subjectivity, and psychosocial factors are mostly related to the differences of migraine and TTH pathophysiology between women and men.